Determination of the fracture parameters of concrete with improved wedge-splitting testing. (December 2022) - Sun, Liguo; Du, Chengbin; Ghaemian, Mohsen; Zhao, Wenhu
Highlights: Springs are installed on the wedge-splitting device to restrain quasi-brittle fracture. The strain distribution presents a polynomial deflection curve in the splitting specimen. The crack propagation speed increases as the crack propagates, until reaching a peak value. Complete load–strain curves are recorded to determine the fracture parameters. Abstract: Considering the quasi-brittle mechanical properties of concrete, wedge-splitting tests are employed and improved in this paper to study the fracture behaviour of concrete. A novel wedge-splitting device is designed by fixing ten springs on the force transmission component. The adaptive spring force can be imposed on top of a concrete specimen to retard the brittle fracture process. With the proposed wedge-splitting test design for notched cuboid specimens, the complete load–strain/CMOD curves of concrete can be generated directly. The fracture toughness and the fracture energy can be calculated easily without numerical fitting using the double-K fracture model. The descending branch of the curve is verified by exponential and power function fitting, where the maximum relative error is approximately 15% and the average relative error is less than 6%. Moreover, the specimen strain distribution presents a polynomial deflection curve, with the upper part of the specimen in tension and the lower part of the specimen in compression, and the initial zero point is located at a crack growth ratio of approximately 0.53 relative to the whole fracture path. The concrete fracture process consists of an initial stage of crack growth, a long-term stable propagation stage, and an unstable propagation stage.